Flow along tool-chip interface in orthogonal metal cutting - Enahoro, H. E.; Oxley, P. L. B. (College of Aeronautics, 1965)
In recent papers it has been suggested that over part of the toolchip contact zone the chip does not slide but sticks to the tool, chip flow taking place by shear within the body of the chip. Sticking contact is inconsistent with steady state cutting and in this paper a slip-line field model of chip flow is presented which does not include sticking contact and which is consistent with the relevant experimental observations.